2017
DOI: 10.1016/j.rbre.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

New guidelines for the diagnosis of fibromyalgia

Abstract: Evidence collection was performed based on 9 questions regarding the diagnosis of fibromyalgia, structured using the Patient, Intervention or Indicator, Comparison and Outcome (P.I.C.O.), with searches in the main, primary databases of scientific information. After defining the potential studies to support the recommendations, they were graded according to evidence and degree of recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 49 publications
1
26
0
9
Order By: Relevance
“…Regarding pharmacological treatment, 53.8% of the patients used antidepressants, a proportion that may be considered low, since international recommendations for the treatment of FM indicate antidepressants as the first treatment line 9 . The nursing intervention analyzed in this study is in line with the recommendations of the Brazilian Consensus for the treatment of FM, which reaffirms the importance of guidelines and programs for self-control of pain [17][18][19] . Therefore, nursing intervention with telephone monitoring was an effective strategy to improve treatment outcomes in patients with FM, confirming the efficacy of the recommendations of the national and international consensus for the treatment of this syndrome.…”
Section: Discussionsupporting
confidence: 76%
“…Regarding pharmacological treatment, 53.8% of the patients used antidepressants, a proportion that may be considered low, since international recommendations for the treatment of FM indicate antidepressants as the first treatment line 9 . The nursing intervention analyzed in this study is in line with the recommendations of the Brazilian Consensus for the treatment of FM, which reaffirms the importance of guidelines and programs for self-control of pain [17][18][19] . Therefore, nursing intervention with telephone monitoring was an effective strategy to improve treatment outcomes in patients with FM, confirming the efficacy of the recommendations of the national and international consensus for the treatment of this syndrome.…”
Section: Discussionsupporting
confidence: 76%
“…It is estimated that updating the FMS classification criteria, as well as the increased acceptance of the diagnosis, may directly influence the increase in the indicated values of prevalence. FMS has its classification criteria established by American College of Rheumatology 11 and these are widely discussed in Brazil in groups of rheumatologists 12 and groups of studies of pain 13 . Most of the cases in this study reported consulting -mainly -rheumatologists, followed by pain specialists.…”
Section: Discussionmentioning
confidence: 99%
“…According to the American College of Rheumatologist [4], the new diagnostic criteria reveal that the patient should have a generalized pain index with a score greater than seven, a severity index of symptoms including fatigue, non-restorative sleep, cognitive symptoms, and somatic symptoms with scores greater than five, in addition to the symptom index is greater than or equal to nine. Symptoms should have been present for at least three months and the patient should have no other problem explaining the symptoms.…”
Section: Introductionmentioning
confidence: 99%